Enterobacter cloacae, an Endophyte That Establishes a Nutrient-Transfer Symbiosis With Banana Plants and Protects Against the Black Sigatoka Pathogen - Macedo-Raygoza, Gloria M.; Valdez-Salas, Benjamín; Prado, Fernanda M.; Prieto, Katia R.; Yamaguchi, Lydia F.; Kato, Massuo J.; Canto-Canché, Blondy B.; Carrillo-Beltrán, Monica; Di Mascio, Paolo; White, James F.; Beltrán-García, Miguel J. (Frontiers in Microbiology, 2019)
Banana (Musa spp.) is an important crop worldwide, but black Sigatoka disease caused by the fungus Pseudocercospora fijiensis threatens fruit production. After exhaustive isolation of endophytic microbes from banana plants, we examined the potential of Enterobacter cloacae and Klebsiella pneumoniae to transfer organic nitrogen and support plant growth in nutrient limited soils. Both bacteria were also found to be antagonistic against P. fijiensis strains. The two bacterial isolates were identified by MALDI-TOF mass spectrometry and corroborated by 16rRNA sequence analysis. Plant growth promotion (PGP) traits, including nitrogen fixation, phosphate solubilization, indole-3-acetic acid (IAA) and siderophore production, and ACC deaminase (ACCd), were evaluated using microbiological approaches. To measure the effects on plant growth, the two plant bacteria and an E. coli as non-endophyte, were inoculated weekly for 60 days as active cells (AC) and heat-killed cells (HKC) into plant microcosms without nutrients and compared to a water only treatment, and a mineral nutrients solution (MMN) treatment. All bacterial treatments stimulated growth parameters and prevented accelerated senescence, which was observed for water and mineral nutrients solution (MMN) treatments (controls). Of the bacterial treatments, only the E. cloacae (AC) treatment resulted in a sustainable symbiosis with banana plants. After 60 days, only those plants inoculated with E. cloacae showed intracellular bacteria within root cells. Plants died after 15 days of being irrigated with water; irrigation with MMN enabled plants to develop some new leaves, but plants lost weight (-30%) during the same period. To evaluate the transference of organic N from bacteria into the plants, bacteria were labeled with 15NH4Cl or Na15NO3. The 15N on plant tissues was measured by pheophytin isotopomers abundance. The relative abundance of the isotopomers m/z 872.57, 873.57, 874.57, 875.57, 876.57 unequivocally demonstrate that plants acquire 15N atoms directly from bacterial cells, using them as a source of N, to favor plant growth in nutrients absence. These results reveal a new alternative to promote growth and health of crops using endophytic bacteria such as E. cloacae as an alternative to agrochemicals for banana cultivation.